Case Report: Coronary plaque rupture following glucocorticoid tapering in a high-risk CAD patient with immune nephritis: mechanistic insights and clinical implications - Weng, Jianxin; Piao, Fushi; Lai, Ruihui; Chen, Wenwen; Sun, Shuai; Xu, Tan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundGlucocorticoids (GCs) exhibit metabolic risks that may accelerate atherosclerosis. However, their in vivo effects on atherosclerotic plaques remain poorly understood. This case highlights the perilous interplay between chronic GC use and plaque vulnerability during dose reduction.Case summaryA 51-year-old male with immune nephritis, chronic kidney disease (CKD), and poorly controlled hypertension presented with unstable angina. Coronary angiography revealed multivessel disease [70% stenosis in the proximal left anterior descending artery (LAD) and 90% in the posterior descending artery]. Initial treatment included angioplasty with a drug-coated balloon in the posterior descending artery, dual antiplatelet therapy, statins, and prednisone (10 mg/day). Seven months later, after self-reducing GCs to 5 mg/day, he suffered an acute myocardial infarction due to LAD plaque rupture, confirmed by optical coherence tomography (OCT) showing fibrolipid-rich plaques, deep calcifications, and minimal lumen area (0.67 mm2). Emergency stenting was performed to stabilize the patient, with no recurrence at 3-month follow-up.DiscussionThis case underscores the mechanistic duality of GCs. Chronic GC therapy suppresses pro-inflammatory cytokines and macrophage activity, stabilizing plaques by reducing oxidized LDL uptake. However, abrupt tapering may trigger rebound vascular inflammation, destabilizing high-risk lesions. OCT imaging proved critical in identifying vulnerable plaque morphology, emphasizing its role in guiding urgent interventions.